Effectiveness and Safety of Prolonged Needle Decompression Procedures in Tension Pneumothorax Patients with COVID-19 - Koeshardiandi, Mirza; Wicaksana, Zulfikar Loka; Semedi, Bambang Pujo; Avidar, Yoppie Prim (Indonesian Journal of Anesthesiology and Reanimation, 2022)
Introduction: Coronavirus disease-19 (COVID-19) has become a pandemic that is still ongoing today. This is a new challenge for health workers in handling emergency cases. Several COVID-19 patients arrived at the hospital with severe respiratory problems. Meanwhile, other pathological conditions causing respiratory failure must also be considered, such as pneumothorax. Objective: This study aimed to examine the effective emergency procedures to treat COVID-19 cases with tension pneumothorax. Case Report: A 45-year-old male patient arrived with a referral letter from a pulmonologist with a diagnosis of simple pneumothorax and pneumonia. The patient also presented a positive SARS COV-2 PCR test result. The patient complained about a worsening of shortness of breath. A symptom of dry cough for 14 days was also reported. Chest radiograph examination subsequently indicated right tension pneumothorax. In the emergency ward, needle decompression procedure connected to the vial containing sterile intravenous fluids was performed. Re-examination of the chest x-ray demonstrated right pulmonary re-expansion. The patient was monitored and after four days, needle decompression was removed and no chest tube was inserted because complete resolution of the lungs had occurred. This case illustrates that tension pneumothorax causes worsening of the patient's condition with COVID-19 diagnosis. In another case of tension pneumothorax in a COVID-19 patient, needle decompression of the 2nd intercostal space and the mid-clavicular line was performed as initial treatment followed by chest tube insertion as definitive treatment. However, in this case, chest tube approach was not carried out because the patient had demonstrated clinical and radiological improvement and a worsening condition had not occurred. Conclusion: Prolonged needle decompression connected to a vial containing sterile intravenous fluids as deep as 2 cm from the water surface is an effective procedure in the management of tension pneumothorax even without the installation of a chest tube.